EAN guideline on palliative care of people with severe, progressive multiple sclerosis. (29th May 2020) - Solari, A.; Giordano, A.; Sastre‐Garriga, J.; Köpke, S.; Rahn, A. C.; Kleiter, I.; Aleksovska, K.; Battaglia, M. A.; Bay, J.; Copetti, M.; Drulovic, J.; Kooij, L.; et al.
Abstract : Background and purpose: Patients with severe, progressive multiple sclerosis (MS) have complex physical and psychosocial needs, typically over several years. Few treatment options are available to prevent or delay further clinical worsening in this population. The objective was to develop an evidence‐based clinical practice guideline for the palliative care of patients with severe, progressive MS. Methods: This guideline was developed using the Grading of Recommendations Assessment, Development and Evaluation methodology. Formulation of the clinical questions was performed in the Patients–Intervention–Comparator–Outcome format, involving patients, carers and healthcare professionals (HPs). No uniform definition of severe MS exists: in this guideline, constant bilateral support required to walk 20 m without resting (Expanded Disability Status Scale score > 6.0) or higher disability is referred to. When evidence was lacking for this population, recommendations were formulated using indirect evidence or good practice statements were devised. Results: Ten clinical questions were formulated. They encompassed general and specialist palliative care, advance care planning, discussing with HPs the patient's wish to hasten death, symptom management, multidisciplinary rehabilitation, interventions for caregivers and interventions for HPs. A total of 34 recommendations (33 weak, 1 strong) and seven good practice statements were devised. Conclusions: The provision of home‐based palliative care (either general or specialist) is recommended with weak strength for patients with severe, progressive MS. Further research on the integration of palliative care and MS care is needed. Areas that currently lack evidence of efficacy in this population include advance care planning, the management of symptoms such as fatigue and mood problems, and interventions for caregivers and HPs.